Estudo retrospectivo das neoplasias mesenquimais caninas diagnosticadas no setor de patologia animal da EVZ/UFG - Silva, Ashbel Schneider da (2020)
The number of dogs with neoplasms is increasing, and some occur more frequently in animals of certain breeds, sex and age, factors relevant to the direction of diagnosis by the veterinarian. The diversity of neoplasms in dogs can vary geographically due to differences in susceptibility, environmental factors and habits. Therefore, studies and research on frequency, prevalence, tumor type, biological behavior and origin of the neoplasm are relevant. Thus, this study aimed to carry out a retrospective study on canine mesenchymal neoplasms diagnosed in the Animal Pathology Service of the School of Veterinary and Zootechnics of the Federal University of Goiás (SPA/EVZ/UFG), Goiânia, GO, over a period of twelve years, emphasizing epidemiological data, macroscopic aspects and histomorphological classification. In 32 cases in which the neoplasms were diagnosed as undifferentiated or anaplastic, an immunohistochemical study with antivimentin antibody was performed, aiming to confirm the mesenchymal embryonic origin of these tumors, all of which marked positively for the tested antibody. Thus, 623 mesenchymal neoplasms were cataloged from 2006 to 2018. Of these, 72% referred to those with malignant behavior. Pitbull, Boxer, Poodle, Dachshund and Pinscher dogs were the breeds most affected, and females (64.4%) were the most diagnosed with mesenchymal neoplasms. Most mesenchymal tumors were small and medium in size and occurred more frequently in elderly animals (59.6%). Of the tumor types, the most frequent ones were mast cells tumors (n=146, 23.4%), hemangiosarcomas (n=95, 15.2%) and melanomas (n=67, 10.7%). In conclusion, mesenchymal tumors commonly present malignant behavior, affecting more often purebred canines, females and the elderly, with mast cell tumor being the most frequent mesenchymal neoplasia.